Synthesis of Ureido-Muraymycidine Derivatives for Structure Activity Relationship Studies of Muraymycins - Aleiwi, Bilal A. (2012)
One of the key constituents of the muraymycins is the 6-membered cyclic guanidine, (2S,3S)-muraymycidine (or epi-capreomycidine). In order to diversify the structure of the oligo-peptide moiety of the muraymycins for thorough structure activity relationship studies, we have developed a highly stereoselective synthesis of ureido-muraymycidine derivatives with the lactone 4a.